OJUH DALAM PERTUNJUKAN BUKOBA CERITA PANGLIMA AWANG DI PASIR PANGARAIAN - Muslim Muslim; Sulaiman Juned; Edwar Zebua (Jurnal Ilmu Budaya, 2023)
Ojuh is an allure in the staging of bukoba even though it is not the main element in bukoba. It can be ascertained if the staging of bukoba is not a story that uses Ojuh, not interesting in the staging of bukoba. This research was structured with the aim of investigating and explaining ojuh in bukoba Panglima Awang story shows and explaining the symbolic meaning in Panglima Awang book bukoba story in Pasir Pangarain. This research used a descriptive qualitative method. To answer the problem formulation the researchers directly observed the staging of bukoba. To See the process of the Bukoba story Panglima Awang's performance. Direct observations with bukoba koba (speaker) is done. Researchers used interview techniques, recorded videos, and field notes in the process of collecting data. The participant in this study was Tuk Taslim a carpenter (speaker). The conclusions of the analysis of the meaning of this ojuh, which is something that is excessive, things that are delivered excessively, deliberately done, created in the context of creating trades in the book performance, through ways (techniques, skills, art) such as this is thing audience finally want to wateh this performance. Then, it turns out that ojuh in the kang Panglima Awang implies the meaning of leadership owned by Awang and Anggun Cik Suri. The beauty of Anggun Cik Suri has, the strength that Awang has.